THE ROLE OF INTERNATIONAL DOCUMENTARY PAYMENT INSTRUMENTS IN COMMODITY CIRCULATION - Murillo Córdoba, Martín (2013)
Countless transactions take place on a daily basis at a global level. Nations exchange their products according to their production purpose; however, this usually happens within the circuit of capital model. In one of this model´s stages, i.e. commodity circulation, international documentary payment instruments (IDPI) have a crucial role. Even though these instruments do not carry commercial value, they represent completely the will of the economic agents who use them to achieve the incremental value they expect. This article is aimed at addressing the role of IDPIs in commodity circulation.